House of Netflix: Streaming media and digital lore. (2nd January 2019) - Burroughs, Benjamin
ABSTRACT: This article focuses on the emergence of a nascent streaming industry. The media industry studies conceptualization of "industry lore" can be read during times of transition for media industries. Streaming lore is a re-articulation of existing industry lore accompanying the advent of streaming technology and distribution. Contemporary streaming acts as a site of rupture, wherein industry discourses related to digital media are rendered visible. The article proposes three categories of emergent streaming lore and analyzes their relation to a growing streaming media industry. These categories include (a) Netflix as "quality" streams, (b) the algorithmic audience, and (c) cord-cutters and cord-nevers.